The worlds religions in figures : an introduction to international religious demography - Johnson, Todd M. (Todd Michael), 1958- (Malden, MA : Wiley-Blackwell, 2013)
Provides an introduction to international religious demography, outlining the challenges in interpreting data on religious adherence, and presents a contemporary portrait of global religious belief. Offers the first comprehensive overview of the field of international religious demography detailing what we know about religious adherents around the world, and how we know it.